Manajemen Pembentukan Karakter Kebangsaan melalui Pembelajaran Pancasila - Adisel, Adisel; Thadi, Robeet; Sukarno, Sukarno (JOPPAS: Journal of Public Policy and Administration Silampari, 2024)
This study explores how managing the formation of national character through pancasila learning at the College of Islamic Religion. The approach used research qualitative descriptive methods. There are 10 informants represented by faculty members of the consortium and program coordinators involved in the preparation and evaluation of curricula, lecturers who teach pancasila mathematics, selection of informants using purposive sampling techniques, data obtained through interviews and documentation. The results of the study that management of formation of national character through learning Pancasila in Islamic Religion College in an effort to develop the national character of good students, that is, students have behaved respectfully, honest, disciplined and responsible in the campus or in the community environment this proves the absence of reports of citizens for bad behavior. The learning environment is a region with all its content that is interrelated with the learning activities have a strong influence on the application of blended learning. Prasarana and supporters at the major can support the application of blended learning. Keywords: Management, National Character, Learning Pancasila.